Computer application for bilinear system identification. (4th August 2014) - DoriBen, Hans–Theo; Schwarz, Helmut
The problem of realisation and parameter identification of bilinear systems from recorded input/output data is discussed. First, a brief review of the existing results in realisation theory is given. Then standard results from linear systems theory, such as the Markov parameter representation, Hankel matrices, the algebraic input/output model and the equivalent discrete–time system are transferred to bilinear systems theory. Finally, the advantage of applying computing to the identification problem is outlined and demonstrated for a suitable model of a hydraulic drive.